Novel Cell Therapy Using Mesenchymal Stromal Cell Sheets for Medication-Related Osteonecrosis of the Jaw - Kaibuchi, Nobuyuki; Iwata, Takanori; Koga, Yoko Kawase; Okamoto, Toshihiro (Frontiers in Bioengineering and Biotechnology, 2022)
Despite medication-related osteonecrosis of the jaw (MRONJ) being first reported in 2003, the optimal treatment and prevention modalities for MRONJ are not clear. As a result, dentistry, oral surgery, and departments involved in the treatment of cancer and bone diseases are struggling with the management of MRONJ. Several cases of MRONJ cannot be managed by conventional treatment strategies recommended in various position papers. Therefore, studies have been conducted to investigate the efficacy of novel therapies for MRONJ. However, the optimal treatment is unknown. Several cell therapies including autologous cell transplantation have been reported for MRONJ. Although the efficacy of cell therapy for MRONJ has been demonstrated, large, statistically accurate clinical trials are lacking. We have been investigating the efficacy of MRONJ treatment using mesenchymal stromal cell (MSC) sheets since 2013 and confirmed its efficacy through various experiments, wherein MSC sheets were transplanted in model rats and beagle dogs with MRONJ-like lesions. Based on these results, we are planning to conduct a clinical trial of MRONJ therapy using periodontal ligament-derived MSC sheets.